THE ACQUISITION OF SPEECH PATTERN BY TWO-YEAR-OLD KARONESE GIRLS - Sri Apulina br Ginting and Meisuri (LINGUISTICA, 2016)
This research analyzes the acquisition of speech pattern by three Karonese girls. Particular attention is given to types of speech pattern acquired by the three girls. This research uses ethnography qualitative research. The term ethnography has come to be quated with vitually any qualitative research project where the intent is to provide a detailed, in depth description of everyday life and practice. The data were collected by applying documentary technique through daily observation in different context when the children should be active and produce utterances such as playing, watching television, having snack, home activities and communicate with others. The finding at this research shows that Karonese girls acquired three types of speech patterns, namely one- word utterance, two- word utterances and multi- word utterances. The speech pattern used more complex and accordance with the structure of words in the local Karo language. There were three factors affecting language acquisition of the three children, namely society, cognitive process and language.